IMAJINASI KEBANGSAAN ORANG JAWA DI SURINAME DALAM VIDEO MUSIK POPULER - Adji, Titus Soepono (Seni Media Rekam ISI Surakarta, 2009)
In nowadays context, Javanese people in Suriname seems to be something un expectable. They have been living far away from the mother land since a century ago. This kind condition not only restricted the communication within their ancestors but loose also the access into their cultural and identity references. Who really am I? Where did I Come from ? and What is my goal here? There are some frequent questions. Following the technology, here , is internet , we now able to see that Javanese people in Suriname can say the origin of their Javanese identity. Is it a deconstruction ? or a reflexive media to show their origin identity. Keyword : Javanese, Suriname, identity